Uncovering alleles beneficial for seed characteristics in durum wheat (Triticum durum Desf.) landraces and cultivars - Chegdali, Youssef; Ouabbou, Hassan; Essamadi, Abdelkhalid; Sahri, Ali; Dreisigacker, Susanne; Guzmán, Carlos (Springer, 2024)
Landraces and ancient cultivars offer the potential for re-selecting key traits and alleles that might enhance grain yield. A durum wheat collection consisting of 18 landraces (LAN), 5 Moroccan cultivars (MC), and 11 North American cultivars (NAC) was analyzed for seed characteristics and 14 loci associated with grain weight. The study found significant genetic variation in seed characteristics, with the NAC and MC cultivars having higher mean values compared to LAN. Several accessions displayed promising traits for grain weight and size. The genotyping results showed that there were four polymorphic loci and ten monomorphic loci. The polymorphic loci were Wx-B1, TaCwi-4A, TaGS5-A1, and TaSus1-7B. The monomorphic loci included Wx-A1, TaCwi-A1, TaGW2, TGW6-4A, TaSus1-7A-1185, TaSus1-7A-1599, TaSus1-7A-3544, TaSus2-2A, TaSus2-2B, and TGW6. The highest frequencies of desirable alleles were found in the LAN group, followed by MC and NAC. LAN carried the desirable alleles, Wx-B1b, Hap-4A-T, TaGS5-A1b, and Hap-T, at the Wx-B1, TaCwi-4A, TaGS5-A1, and TaSus1-7B loci, respectively. The number of favorable alleles in each accession was significant, with LAN accession MGB-3083 carrying up to 12 favorable alleles. Additionally, four accessions had 11 favorable alleles, namely MC MGB-22, LAN MGB-3101, and two NAC lines (MGB-66035 and MGB-6606). In conclusion, the current study offers insights for improving durum wheat yield by identifying high genetic variation among desirable characteristics and alleles among accessions, as well as highlighting accessions with excellent allele combinations of important yield-related genes.